Ukraine's Energy Sector Security and Sustainable Development in Light of the War with Russia - Frol Revin (International Society of Philosophy and Cosmology, 2023)
We are swiftly nearing the end of the decade since the United Nations General Assembly adopted a resolution that endorsed an all-encompassing action plan for sustainable development up to the year 2030. The final document, titled "Transforming our World: The 2030 Agenda for Sustainable Development," delineates 17 Sustainable Development Goals (SDGs) and 169 targets, representing an unparalleled global commitment to sustainable collaborative endeavors aimed at a comprehensive and universally synchronized international cooperation initiative. This international commitment seeks to yield advantages for everyone, spanning current and forthcoming generations, while upholding the rights and responsibilities of nations as dictated by international law. Ukraine, as a forward-thinking nation aspiring to integrate seamlessly into the rapidly evolving European and global community, lends its support to the pursuit of the SDGs. Consequently, acknowledging the distinctive context of our country's progress, Ukraine has crafted the "Sustainable Development Goals: Ukraine" National Report. In December 2020, the Cabinet of Ministers of Ukraine underscored the significance of incorporating the SDGs into the conception and execution of all pertinent facets of state policy. As a result, the SDGs have evolved into guiding tenets on the domestic stage, molding both programmatic and anticipatory documents. The latest energy security assessments by the United Nations Development Programme (UNDP) underscore the substantial repercussions stemming from disruptions to pivotal substations and major generation facilities, including thermal power plants and combined heat and power plants (CHPs), on critical urban infrastructure. The centralized generation framework also poses obstacles to consumption regulation and hampers the assimilation of renewable energy sources, such as solar and wind, which are pivotal for curtailing carbon dioxide emissions.To tackle these issues, coupled with the devastating effects of Russian military aggression, it is crucial to develop additional maneuvering capacities within the power system. Constructing modern, highly maneuverable, and environmentally friendly generation facilities, including thermal biomass plants, electricity storage systems, and hydroelectric storage facilities, dispersed throughout the territory, will enhance system flexibility and promote the utilization of renewable energy sources. Increasing the share of renewables in the power system is a priority. Implementing strict regulations on solar power plant construction without energy storage devices and coordinating the development of wind generation capacities with the expansion of flexible power generation capacities are necessary steps to achieve sustainable growth in the energy sector.